Collaborative governance in forestry issues: A bibliometric analysis with VOS viewer software using Scopus database - Wicaksono, Agung (International Journal of Innovative Research and Scientific Studies, 2023)
This study aims to analyse scientific literature on collaborative governance in forestry issues published from 2001 to 2022. To ensure paper quality, the study will use VOSviewer software to visualise the bibliometric analysis from Scopus Database. Bibliometric analysis was used to analyse 72 papers about collaborative governance in forestry issues. VOSviewer software visualised publishing trends, country/institution/author contributions, journal distribution, highly cited articles, bibliographic coupling analysis, and keyword analysis. According to the study, collaborative governance in forestry publications has increased considerably in the last decade. Most research on this issue comes from the US, Canada, and Australia. Colorado State campus was the study’s most affiliated campus, followed by Saskatchewan and Oregon. This study was published in Land Use Policy, Society and Natural Resources, and Ecology and Society. The combination of bibliographies and keyword concurrency networks showed that collaborative governance in forestry issues is closely linked to sustainable development, environmental governance, and forest governance. The study finds that collaborative governance in forestry issues needs more research, especially with collaborative governance as a framework. The bibliometric analysis provides a complete overview of publishing trends, country/institution/author contributions, journal distribution and highly cited articles, bibliographic coupling analysis, and keyword analysis in this field. Researchers, policymakers, and practitioners interested in collaborative governance in forestry may profit from the study. The results may identify key contributors, influential journals, and critical study areas linked to this topic.